KONFLIK BATIN TOKOH UTAMA DALAM CERPEN THE DOCTOR AND THE DOCTOR’S WIFE KARYA ERNEST HEMINGWAY - Murdianto, Bambang Tri (Balai Bahasa Jawa Tengah, 2017)
This research examines the inner conflict of the main character in the short story The Doctor and the Doctor?s wife by Ernest Hemingway. The purpose of this study is to describe the inner conflict and background of inner conflict in the short story The Doctor and the Doctor?s wife. This reasearch is qualitative. The research method is descriptive analysis, Descriptive analyzes carried out by way of description of the facts which are then followed by analysis. By looking at the data contained in the short story The Doctor and the Doctor?s wife by Ernest Hemingway, in which it is to reveal inner conflict of the main character, background of inner conflict, eksternal factor and internal factor. From the conclusion of the data analysis, inner conflict of the main character is emergence of fear, hesitancy, and anger caused by non-fulfillment of? physiological needs, honor, security, self-actualization on main character. The inner conflict event influenced by aspect id,ego, and superego.? Inner conflict the main character is more concerned with statisfying the id with ego. Superego functioning resulting in only in some cases.